Upaya Meningkatkan Perilaku Masyarakat Tentang Pencegahan Penularan Covid-19 Melalui Promosi Kesehatan Dan Penerapan Kebijakan Pemerintah Daerah Di Kota Surabaya - Hari Kristianto; Ceria Nurhayati (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
The COVID-19 pandemic is a disaster that heartbreaks all the inhabitants of the earth. Corona Virus Disease 2019 is a new type of disease caused by infection with the Severe Acute Respiratory Syndrome Coronavirus 2 Virus (SARS- COV-2) or known as the novel coronavirus (2019-nCoV). The research design used in this study is descriptive analytic, with the aim of proving the influence of health promotion and the implementation of policies on preventing the transmission of COVID-19 on people's behavior. The results of this study found that there was a change in respondents' behavior before being given health promotion and after being given health promotion, from the results above it can be interpreted that changes in respondents' behavior in a positive direction marked with a positive rank of 107, and the results of statistical tests using the wilcoxon test were obtained p = 0.000 which means that if p < 0.05, then there is a change in behavior before being given treatment with after being given treatment.  Based on research efforts to improve community behavior about preventing covid-19 transmission through health promotion and the implementation of local government policies in the city of Surabaya, it can be concluded that there is a change in behavior in respondents